2002
DOI: 10.1159/000057869
|View full text |Cite
|
Sign up to set email alerts
|

Lactoperoxidase Inhibits Glucosyltransferases from <i>Streptococcus mutans </i>in vitro

Abstract: This study examines the possible effect of the antimicrobial peroxidase system on the activity of streptococcal glucosyltransferases B, C and D (GtfB, GtfC and GtfD), either in solution (GtfB and GtfC) or when adsorbed to hydroxyapatite (GtfC and GtfD) at pH 6.5. The lactoperoxidase (LP) system (LP, H2O2, SCN) had no effect on the activity of dissolved GtfC, but the activity of dissolved GtfB was enhanced. The LP system, however, strongly inhibited the activities of both GtfC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…In addition, Gtfs also bind to other components of the salivary pellicle such as salivary peroxidase, amylase and lysozyme [Korpela et al, 2002; Hannig et al, 2005; Kho et al, 2005]. Available data shows clearly that Gtfs interact with salivary amylase in pellicle [Vacca-Smith et al, 1996a] inhibiting activity and blocking adsorption of salivary amylase to HA [Hannig et al, 2005].…”
Section: Role Of Gtfs In Dental Plaque Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Gtfs also bind to other components of the salivary pellicle such as salivary peroxidase, amylase and lysozyme [Korpela et al, 2002; Hannig et al, 2005; Kho et al, 2005]. Available data shows clearly that Gtfs interact with salivary amylase in pellicle [Vacca-Smith et al, 1996a] inhibiting activity and blocking adsorption of salivary amylase to HA [Hannig et al, 2005].…”
Section: Role Of Gtfs In Dental Plaque Formationmentioning
confidence: 99%
“…Available data shows clearly that Gtfs interact with salivary amylase in pellicle [Vacca-Smith et al, 1996a] inhibiting activity and blocking adsorption of salivary amylase to HA [Hannig et al, 2005]. Lactoperoxidase in the absence of substrates, which is structurally and enzymatically similar to salivary peroxidase, inhibits all 3 Gtf enzymes in solution or adsorbed to sHA beads [Korpela et al, 2002]. The presence of lysozyme reduced the activity of GtfB in solution and on a surface but was without apparent effect on the structure of glucan formed [Kho et al, 2005].…”
Section: Role Of Gtfs In Dental Plaque Formationmentioning
confidence: 99%
“…As an agonist of lysozyme, peroxidase inhibits the adherence of S. mutans to hydroxyapatite (78, 88, 89). However, peroxidase also inhibits glucosyltransferase immobilized in pellicles on hydroxyapatite (90).…”
Section: Peroxidasesmentioning
confidence: 99%
“…Cawley et al demonstrated that the LPO system together with lactoferrin, lysozyme, and bovine milk immunoglobulins have the ability to inhibit the formation of single-species S. mutans biofilm, whereas, in the case of multispecies biofilms (which more accurately represents biofilms occurring in vivo), its application resulted in the loss of microbial viability without the decrease in biofilm mass [141]. This fact can be explained by the ability of the LPO system to kill microorganisms, but the inability to inactivate glucosyltransferases, i.e., extracellular bacterial enzymes responsible for the synthesis of glucans building a biofilm matrix [142].…”
Section: Biological Role Of the Lpo Systemmentioning
confidence: 99%